Modifications in dietary and alcohol intakes between before and after cancer diagnosis: Results from the prospective population‐based NutriNet‐Santé cohort. Issue 3 (15th May 2017) - Fassier, Philippine; Zelek, Laurent; Lécuyer, Lucie; Bachmann, Patrick; Touillaud, Marina; Druesne‐Pecollo, Nathalie; Galan, Pilar; Cohen, Patrice; Hoarau, Hélène; Latino‐Martel, Paule; Kesse‐Guyot, Emmanuelle; Baudry, Julia; et al.
Abstract : Postdiagnosis diet and alcohol consumption may be associated with cancer prognosis, recurrence and mortality. Our aim was to investigate food, nutrient and alcohol intake variations between before and after cancer diagnosis and their determinants in a prospective cohort. Subjects ( n = 696) were incident cancer cases diagnosed in the NutriNet‐Santé cohort between 2009 and 2016. Food, nutrient and alcohol intakes were prospectively collected using repeated nonconsecutive 24‐hr dietary records since subjects' inclusion ( i.e . an average of 2 y before diagnosis). Mean number of dietary records per subject was 5.9 before and 8.1 after diagnosis. All dietary data before and after diagnosis were compared by mixed models. Factors associated with the main dietary changes observed were also investigated using multivariable logistic regressions. We observed a decrease in intakes of vegetables (mean decrease in intake in patients who decreased their intake=‐102.4 ± 79.8 g/d), dairy products (–93.9 ± 82.8 g/d), meat/offal (–35.5 ± 27.8/d), soy products (–85.8 ± 104.1 g/d), sweetened soft drinks (–77.9 ± 95.4 g/d), and alcoholic drinks (–92.9 ± 119.9 g/d), and an increase in broths (42.1 ± 34.9 g/d) and fats/sauces (18.0 ± 13.4 g/d). We observed a decrease in energy intake (–377.2 ± 243.5 kcal/d) and in intakes of alcohol (–7.6 ± 9.4 g/d) proteins (–17.4 ± 12.5 g/d), and several vitamins ( p < 0.05) and micronutrients ( p < 0.05). Conversely, lipid (19.4 ± 14.6 g/d), SFA (9.3 ± 7.0 g/d), MUFA (8.3 ± 6.3 g/d) and vitamin E (3.9 ± 3.3 mg/d) intakes increased after diagnosis. This large prospective study suggests that cancer diagnosis is a key period for nutritional changes. It highlights some healthy behaviors such as a decrease in alcohol and sweetened drink consumption, but also less favorable trends, such as a decrease in vegetable consumption and in many vitamin and mineral intakes. These results provide insights to identify and target recommendations to put forward for better nutritional care of cancer survivors. Abstract : What's new? Postdiagnosis diet and alcohol consumption may be associated with cancer prognosis, recurrence and mortality. In this study, the authors analyzed the socio‐demographic, economic, lifestyle and clinical factors associated with these dietary changes. They found that, while there was a decrease in alcohol consumption, there were a number of less favorable trends, such as decreased vegetable consumption and nutrient intake. These results offer insights to identify and target dietary recommendations to improve prognosis and quality of life for cancer patients.